Derecho indígena al territorio y a la consulta: el caso yaqui en México - Magdalena Gómez (e-cadernos ces)
In this essay I focus on the paradigmatic case of the Yaqui tribe’s resistance against the construction of the Acueducto Independencia (Independence Aqueduct), with a view to analyze the politics and legal strategies of territorial defense, the role of indigenous rights, and the positions and criteria of the Supreme Justice Court of the Nation (Suprema Corte de Justicia de la Nación). Finally, I present the lack of justiceability regarding indigenous people’s rights. It is important to mention that the analytical emphasis of this article is situated in the critical law field, acknowledging however that there is a very wide historiography about this indigenous people, who, as the other cultures in North Mexico, should not be placed under a Mesoamerican perspective.